Genotype × diet interaction in Uzbek breeds and hybrids of the silkworm (Bombyx mori) for enabling year-round sericulture - MIRZAKHODJAEV BAKHTIYAR; MIRZAKHODJAEV ANVAR; ISMATULLAYEVA DILORAM; TAJENOVA ARZIGUL; RAJABOV ISMOIL (Asian Journal of Agriculture, 2025)
Abstract. Bakhtiyar M, Anvar M, Diloram I, Arzigul T, Ismoil R. 2025. Genotype × diet interaction in Uzbek breeds and hybrids of the silkworm (Bombyx mori) for enabling year-round sericulture. Asian J Agric 9: 808-817. Sericulture in Uzbekistan faces seasonal limitations due to dependence on fresh mulberry leaves, limiting cocoon production to one or two cycles per year. This study evaluated the interaction between genotype and diet type in ten Bombyx mori genotypes—five pure breeds (Ipakchi-5, UzNIISH-9, Ipakchi-1, Gulshan, and Nafis) and five hybrids (Zarafshon, Gulshan × Nafis, Oltin Vodiy, Kumush Tola, and Navruz)—to assess adaptability to artificial feeding for year-round sericulture. Larvae were reared on four diets: freeze-dried mulberry leaves, convectively dried leaves, a Japanese standard artificial diet, and natural leaves as a control. Biological and technological traits were analyzed using two-way ANOVA (Diet × Genotype) and Tukey’s HSD test. Results showed significant effects of both diet and genotype (p<0.001). The freeze-dried mulberry diet ensured the highest survival (86-90%), cocoon weight (1.7-1.85 g), and silk ratio (18.5-20.3%), statistically comparable to natural feeding. Hybrids Gulshan × Nafis and Navruz exhibited superior adaptability and physiological stability, confirming strong genotype × environment interaction. The study demonstrates that locally developed freeze-dried diets enable sustainable, year-round, and industrially scalable sericulture in Uzbekistan, supporting both traditional textile and emerging biomedical applications of silk.